2012
DOI: 10.1103/physreve.85.016328
|View full text |Cite
|
Sign up to set email alerts
|

Long-wave Marangoni convection in a thin film heated from below

Abstract: We consider long-wave Marangoni convection in a liquid layer atop a substrate of low thermal conductivity, heated from below. We demonstrate that the critical perturbations are materialized at the wave number K ∼ √ Bi, where Bi is the Biot number which characterizes the weak heat flux from the free surface. In addition to the conventional monotonic mode, a novel oscillatory mode is found. Applying the K ∼ √ Bi scaling, we derive a new set of amplitude equations. Pattern selection on square and hexagonal lattic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
75
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(79 citation statements)
references
References 40 publications
3
75
0
1
Order By: Relevance
“…In contrast to [12] and several other papers [9,10,11,15,19,20] where longwave oscillatory convection is described by a pair of partial differential amplitude equations, the nonlinear dynamics for the thermocapillary and solutocapillary convection in a layer of binary mixture with a nondeformable free surface is governed by the solvability conditions for a certain set of linear nonhomogeneous equations [22]. In other words, the nonlinear dynamics is described by a set of nonlocal amplitude equations.…”
Section: Introductionmentioning
confidence: 90%
“…In contrast to [12] and several other papers [9,10,11,15,19,20] where longwave oscillatory convection is described by a pair of partial differential amplitude equations, the nonlinear dynamics for the thermocapillary and solutocapillary convection in a layer of binary mixture with a nondeformable free surface is governed by the solvability conditions for a certain set of linear nonhomogeneous equations [22]. In other words, the nonlinear dynamics is described by a set of nonlocal amplitude equations.…”
Section: Introductionmentioning
confidence: 90%
“…Multi-layer film configurations do not, however, guarantee oscillatory modes: for example, such instabilities were not obtained by Pototsky et al (2005) who investigated the dewetting dynamics of isothermal, ultrathin bilayers. Of particular interest to the present work are oscillatory instabilities reported by Shklyaev et al (2012) in a model of thin-film thermocapillary destabilization from below. While there are similarities between that work and the present, we point out one important difference: in Shklyaev et al (2012), the instability is driven by imposing a heat flux at the film-substrate interface; instead, in the present work we consider the full time-dependent heat-transfer in the substrate.…”
mentioning
confidence: 94%
“…We have recently considered the influence of the feedback control on the oscillatory Marangoni instability in a thin film heated from below. We have shown that a linear control gain can delay the onset of instability [3] and a quadratic control gain can eliminate the subcritical excitation of instability [4]. The analysis of pattern formation was done for an infinite region, nonlinear interaction of the traveling waves was considered.…”
Section: Introductionmentioning
confidence: 99%
“…2. There we present a set of coupled amplitude equations which governs the evolution of the layer thickness and the temperature deviation under nonlinear feedback control [4]. In Sec.…”
Section: Introductionmentioning
confidence: 99%